Nowcasting business cycles using toll data - Nikos Askitas; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2011)
Nowcasting has been a challenge in the recent economic crisis. We introduce the Toll Index, a new monthly indicator for business cycle forecasting and demonstrate its relevance using German data. The index measures the monthly transportation activity performed by heavy transport vehicles across the country and has highly desirable availability properties (insignificant revisions, short publication lags) as a result of the innovative technology underlying its data collection. It is coincident with production activity due to the prevalence of just-in-time delivery. The Toll Index is a good early indicator of production as measured for instance by the German Production Index, provided by the German Statistical Office, which is a well-known leading indicator of the Gross National Product. The proposed new index is an excellent example of technological, innovation-driven economic telemetry, which we suggest should be established more around the world.
urn:nbn:de:101:1-201104113953
Keywords: C82; E01; E32; E37; L92; 330; business cycles; data mining; evaluating forecasts; macroeconomic forecasting; new products; transportation; production forecasting; nowcasting; telemetry; Konjunkturindikator; Straßenbenutzungsgebühr; Statistik; Straßengüterverkehr; Gesamtwirtschaftliche Produktion; Konjunkturprognose; Prognoseverfahren; Deutschland